New Diabetes Therapies and Diabetic Kidney Disease Progression: the Role of SGLT-2 Inhibitors - Dekkers, Claire C. J. (Curr Diab Rep, 2018)
PURPOSE OF REVIEW: Sodium-glucose co-transporter 2 (SGLT-2) inhibitors have emerged as a promising drug class for the treatment of diabetic kidney disease. Developed originally as glucose-lowering drugs by enhancing urinary glucose excretion, these drugs also lower many other renal and cardiovascular risk factors such as body weight, blood pressure, albuminuria, and uric acid. Results from the EMPA-REG OUTCOME and CANVAS trials show that these salutary effects translate into a reduction in cardiovascular outcomes and have the potential to delay the progression of kidney function decline. This review summarizes recent studies on the mechanisms and rationale of renoprotective effects. RECENT FINDINGS: Effects of SGLT-2 inhibitors on the kidney are likely explained by multiple pathways. SGLT-2 inhibitors may improve renal oxygenation and intra-renal inflammation thereby slowing the progression of kidney function decline. Additionally, SGLT-2 inhibitors are associated with a reduction in glomerular hyperfiltration, an effect which is mediated through increased natriuresis and tubuloglomerular feedback and independent of glycemic control. Analogous to diabetic kidney disease, various etiologies of non-diabetic kidney disease are also characterized by single nephron hyperfiltration and elevated albuminuria. This offers the opportunity to reposition SGLT-2 inhibitors from diabetic to non-diabetic kidney disease. Clinical trials are currently ongoing to characterize the efficacy and safety of SGLT-2 inhibitors in patients with diabetic and non-diabetic kidney disease. SUMMARY: The glucose-independent hemodynamic mechanisms of SGLT-2 inhibitors provide the possibility to extend the use of SGLT-2 inhibitors to non-diabetic kidney disease. Ongoing dedicated trials have the potential to change clinical practice and outlook of high-risk patients with diabetic (and non-diabetic) kidney disease.